Hidroponik sistem Wick Tanaman Sayuran bagi Kelompok Wanita Tani di Kecamatan Marusu Kabupaten Maros - Ralle, Andi; Rasyid, Rasmeidah; Alimuddin, Suraedah (Jurnal BALIRESO, 2024)
Hydroponics is an innovative plant cultivation technology that is suitable for application to vegetable plants in small yards. Our partner is the Dahlia Women's Farming Group (KWT) located in Temmapadduae Village, Marusu District, Maros Regency. Their daily activities are housewives, they grow various types of vegetables and ornamental plants in their yards, which on average are relatively small with a conventional cultivation system. The aim of this service is to increase the knowledge and skills of partners in implementing the Wick system of vegetable hydroponics which is quite simple, cheap and easy to do in the yard. The forms of activities carried out are counseling, training/plot demonstration, mentoring and evaluation. This service activity provides significant benefits for KWT Dahlia in Marusu District, Maros Regency because it has increased their knowledge and skills from not understanding to understanding/very understanding in cultivating vegetable plants using the Wick hydroponic system in the yard and the growth of vegetable plants obtained is quite good. . This service activity received a positive response from the community and they participated in the entire series of activities with great enthusiasm